Réponses

2013-06-18T19:14:35+02:00

 a = (x + 4)(x - 6) = x^2 - 6x + 4x - 24 = x^2 - 2x -24

 

 b = (-1 + x)(x - 2) = -x + 2 + x^2 - 2x = x^2 - 3x +2

 

 c = (5 - x)(-11 + x) = -55 + 5x + 11x - x^2 = -x^2 + 16x -55

 

===========

Voilà.

N'hésistez pas à me mettre un message si vous avez une question…

2013-06-18T19:20:35+02:00

a= (x+4)(x-6)

      x*x+x*(-6)+4*x+4*(-6)

      x²-6x+4x-24

a=x²-2x-24

 

b=(-1+x)(x-2)

     -1*x-1*(-2)+x*x+x*(-2)

     -1x+2+x²-2x

b=-3x+2²+2

 

c= (5-x)(-11+x)

      5*(-11)+5*x-x*(-11)-x*x

      -55+5x-11x-x²

c=-55-6x-x²